Breaking the silence: Norwegian teachers’ perspectives on adapting language environments for AAC users - Egeland-Eriksen, Siv; Bjørkøy, Ingrid; Pettersen, Marit; Chahboun, Sobh (Frontiers in Education, 2025)
IntroductionMany children experience challenges and limitations in spoken language, necessitating the use of alternative and augmentative communication (AAC) to communicate effectively. Learning to communicate with AAC involves a systematic training process, and it is essential to adapt the language environment to meet the specific needs of AAC users. The study aims to enhance knowledge on establishing a positive language environment for children using AAC.MethodsA qualitative approach was employed, involving three semi-structured interviews with teachers from three distinct units within the same county in Norway. The interviews focused on elements such as teachers’ knowledge and skills in AAC, communication partner and language model, use of communication materials and aids, and attitudes toward AAC.ResultsKey findings highlight that teachers’ knowledge and skills in AAC, the role of communication partners and language models, the availability and use of communication materials and aids, and positive attitudes significantly contribute to creating a positive language environment for children using AAC. These elements enable effective communication and support language development.DiscussionA combination of knowledge and effective organization is essential for prioritizing the creation of a positive language environment. This, in turn, enables children who use AAC to develop and acquire practical language skills that they can use throughout their lives. The study underscores the importance of systematic training, supportive attitudes, and tailored communication resources in enhancing the language environment for AAC users.